2009
DOI: 10.1371/journal.pone.0006786
|View full text |Cite
|
Sign up to set email alerts
|

Episodic Memory in Detoxified Alcoholics: Contribution of Grey Matter Microstructure Alteration

Abstract: Even though uncomplicated alcoholics may likely have episodic memory deficits, discrepancies exist regarding to the integrity of brain regions that underlie this function in healthy subjects. Possible relationships between episodic memory and 1) brain microstructure assessed by magnetic resonance diffusion tensor imaging (DTI), 2) brain volumes assessed by voxel-based morphometry (VBM) were investigated in uncomplicated, detoxified alcoholics.Diffusion and morphometric analyses were performed in 24 alcohol dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 62 publications
2
40
0
Order By: Relevance
“…Pfefferbaum et al (2009), using quantitative fiber tracking derived from DTI, observed defects in microstructural fiber integrity in frontal forceps, internal and external capsules, fornix, and superior cingulate and longitudinal fasciculi. Chanraud et al (2009) examined white matter integrity in conjunction with measures of verbal episodic memory derived from the Free and Cued Selective Reminding Test. The investigators found that low verbal episodic memory performance in alcoholics was associated with structural compromise of axons in frontal, temporal, hippocampal, and parahippocampal regions.…”
Section: The Five Functional Domainsmentioning
confidence: 99%
“…Pfefferbaum et al (2009), using quantitative fiber tracking derived from DTI, observed defects in microstructural fiber integrity in frontal forceps, internal and external capsules, fornix, and superior cingulate and longitudinal fasciculi. Chanraud et al (2009) examined white matter integrity in conjunction with measures of verbal episodic memory derived from the Free and Cued Selective Reminding Test. The investigators found that low verbal episodic memory performance in alcoholics was associated with structural compromise of axons in frontal, temporal, hippocampal, and parahippocampal regions.…”
Section: The Five Functional Domainsmentioning
confidence: 99%
“…Several regions like cingulate cortex, orbitofrontal cortex, thalamus, amygdala, and hippocampus showed a decreased volume in alcohol-dependent patients (Chanraud et al, 2009;Fein et al, 2002;Mechtcheriakov et al, 2007;Wobrock et al, 2009;Wrase et al, 2008). To estimate volumes of specific brain regions, individual GM images of the regions of interest (ROIs) were created based on the individual whole brain GM images revealed from the VBM image processing and the ROI images depicted from the WFU PIC Atlas (Maldjian et al, 2003) using the image calculation function (imgcalc) of SPM8.…”
Section: Image Processingmentioning
confidence: 99%
“…The regions with volume decrease as a consequence of alcohol abuse were found to be distributed over the cerebral cortex, with a focus on the frontal cortex. The parietal and cingulate cortex as well as insula, thalamus, hippocampus, and cerebellum are also affected (Chanraud et al, 2009;Fein et al, 2002;Mechtcheriakov et al, 2007;Wobrock et al, 2009). Fein and colleagues (2009) report decreased volumes persisting after long-term abstinence.…”
mentioning
confidence: 99%
“…Regarding to DTI-function relationships in alcoholism, frontal fibers connecting left and right hemispheres predict performance by alcoholics on a coordinated psychomotor task (Rosenbloom et al 2008), and number of reconstructed fibers running between the pons and the midbrain is related to cognitive flexibility performance of alcoholics (Chanraud et al 2009b). Also, diffusivity values in the hippocampus grey matter, which is lower in alcoholics than in controls, is related to episodic memory impairment (Chanraud et al 2009a). A survey of multiple supratentorial and infratentorial fiber systems in alcoholics indicated that DTI changes were correlated with impairment in speeded performance and postural stability (Pfefferbaum et al 2009a).…”
Section: Dti In Neurological and Psychiatric Conditionsmentioning
confidence: 99%